2018
DOI: 10.3390/molecules23020366
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Sauchinone on UDP-Glucuronosyltransferase (UGT) 2B7 Activity

Abstract: Herb–drug interaction (HDI) limits clinical application of herbs and drugs, and inhibition of herbs towards uridine diphosphate (UDP)-glucuronosyltransferases (UGTs) has gained attention as one of the important reasons to cause HDIs. Sauchinone, an active lignan isolated from aerial parts of Saururus chinensis (Saururacease), possesses anti-oxidant, anti-inflammatory, and anti-viral activities. In pharmacokinetics of sauchinone, sauchinone is highly distributed to the liver, forming extensive metabolites of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Sauchinone (over 98% purity) was provided by Professor Chin Y.-W. (Pharmacognosy Laboratory of Dongguk University, Seoul, Korea) according to the modification of previously reported method [ 48 ]. Hydroxybupropion, 4-hydroxymephenytoin, 6-hydroxychlorzoxazone, S -mephenytoin, and pooled human liver microsomes from a mixed pool of 50 donors (HLMs; BD Ultra Pool HLM 50, cat.…”
Section: Methodsmentioning
confidence: 99%
“…Sauchinone (over 98% purity) was provided by Professor Chin Y.-W. (Pharmacognosy Laboratory of Dongguk University, Seoul, Korea) according to the modification of previously reported method [ 48 ]. Hydroxybupropion, 4-hydroxymephenytoin, 6-hydroxychlorzoxazone, S -mephenytoin, and pooled human liver microsomes from a mixed pool of 50 donors (HLMs; BD Ultra Pool HLM 50, cat.…”
Section: Methodsmentioning
confidence: 99%
“…These herbal constituents might share the same metabolic pathway with the drug, therefore, inhibition of the drug-metabolizing enzyme activity may decrease the drug’s metabolic clearance and increase its level in the body which in turn may lead to toxicity. A recent study reported that sauchinone, an active principle of the herb Saururus chinensis elevated the zidovudine (ZDV) concentration in mice blood by inhibiting UGT2B7 activity [ 15 ]. This can cause haematological toxicity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%